2021
DOI: 10.1038/s41467-021-25894-9
|View full text |Cite
|
Sign up to set email alerts
|

9p21 loss confers a cold tumor immune microenvironment and primary resistance to immune checkpoint therapy

Abstract: Immune checkpoint therapy (ICT) provides substantial clinical benefits to cancer patients, but a large proportion of cancers do not respond to ICT. To date, the genomic underpinnings of primary resistance to ICT remain elusive. Here, we performed immunogenomic analysis of data from TCGA and clinical trials of anti-PD-1/PD-L1 therapy, with a particular focus on homozygous deletion of 9p21.3 (9p21 loss), one of the most frequent genomic defects occurring in ~13% of all cancers. We demonstrate that 9p21 loss conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
78
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 76 publications
12
78
0
2
Order By: Relevance
“…Upregulation of VEGFA at 6p21.1 in C2 could increase the malignancy of tumor cells and was often accompanied by hypoxia, angiogenesis, and immunosuppressive TME, suggesting tolerance to immunotherapy ( Wang et al, 2020 ). 9p21 deletion (CDKN2A/B) in C2 also conferred primary resistance to immune checkpoint therapy ( Han et al, 2021 ). LAMC2 amplification at 1q25.3 could result in gemcitabine resistance via EMT ( Okada et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Upregulation of VEGFA at 6p21.1 in C2 could increase the malignancy of tumor cells and was often accompanied by hypoxia, angiogenesis, and immunosuppressive TME, suggesting tolerance to immunotherapy ( Wang et al, 2020 ). 9p21 deletion (CDKN2A/B) in C2 also conferred primary resistance to immune checkpoint therapy ( Han et al, 2021 ). LAMC2 amplification at 1q25.3 could result in gemcitabine resistance via EMT ( Okada et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, future studies will also investigate whether inclusion of single gene-based DNA biomarkers identified as potentially predictive in one or more tumor types (e.g. STK11, PBRM1, ARID1A, CDNK2A [68][69][70][71][72][73][74][75] or additional immune related genes assessed on the current expanded quantitative expression panel run in parallel with StrataNGS testing can improve the performance of the IRS model. Limited PD-L1 IHC data was available for subjects in the SCMD, and hence we are not able to directly compare performance of IRS and PD-L1 IHC for predicting pembrolizumab benefit; additionally, this limitation also biases against the overall proportion of patients outside of currently approved indications predicted to benefit from pembrolizumab by IRS, as herein we considered all patients in approved tumor types to be in an approved indication, although in many tumor types only a minority of patients are approved for pembrolizumab treatment based on PD-L1 IHC cutoffs.…”
Section: Discussionmentioning
confidence: 99%
“…Its effects mimic those generated by extrinsic manipulations of the cancer cell UPR (64,65), spontaneous UPR during tumor growth in vivo (74), and genetic manipulation of UPR branches (73,74). Of paramount relevance aneuploid cells impart changes to activated T cells such as decreased IFNg and Granzyme B production that are similar to changes reported for CD4 T cells in ascites of ovarian cancer patients (167), or changes in gene expression noted in head & neck and urothelial cancers with an aneuploid switch based on chromosome 9p arm loss or homozygous deletion of 9p21.3 (9p21) (168,169). Aneuploidy also has the potential to fuel inflammation at the tumor-immune interface through the mechanism illustrated herein.…”
Section: Conclusion and Perspectivementioning
confidence: 99%